Malformationen des Zentralnervensystems: Seltene Ursachen eines organischen Wachstumshormonmangels bei Kindern - Dörr, Helmuth-Günther; Bettendorf, M.; Binder, G.; Hauffa, B.; Mohnike, K.; Mueller, H. L.; Reinehr, T.; Stalla, G. K.; Woelfle, J. (Padiatrie und Padologie, 2020)
Background Growth hormone (GH) deficiency is a rare endocrine disease. Diagnosis using laboratory investigations must be followed by contrast agent-enhanced magnetic resonance imaging of the central nervous system (CNS). Objective Overview of rare CNS malformations associated with GH deficiency in children and adolescents. Material and methods This article was prepared based on lectures held within the framework of a workshop of pediatric endocrinologists in Frankfurt/Main in March 2017. During script preparation, the authors came to a consensus regarding the key statements in the present publication. Results Malformations of the CNS are extremely rare. Among these malformations, pituitary hypoplasia has been most frequently described, followed by the empty sella syndrome and the pituitary stalk interruption syndrome. Ectopic neurohypophysis has been reported in patients with isolated GH deficiency. Septum pellucidum agenesia, corpus callosum defects, ectopic pituitary gland and optic nerve hypoplasia have been found in patients with septo-optic dysplasia. Pharmacological tests of GH secretion revealed markedly lower maximum GH concentrations in patients with CNS anomalies. As a rule, patients with combined CNS anomalies show better response to GH treatment than patients with only a single anomaly. Conclusion The availability of data on CNS malformations in children with GH deficiency is unsatisfactory. The data from patients under GH treatment should continue to be documented and analyzed on a systematic basis.
CRIS-Team WoS Importer:2020-05-15